2007
DOI: 10.2527/jas.2007-0081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of barley grain processing and dietary ruminally degradable protein on urea nitrogen recycling and nitrogen metabolism in growing lambs1

Abstract: The objective of this study was to determine how interactions between dietary ruminally degradable protein (RDP) level and ruminally fermentable carbohydrate (RFC) alter urea N transfer to the gastrointestinal tract (GIT) and the utilization of this recycled urea N in rapidly growing lambs fed high-N diets. Four Suffolk ram lambs (34.8 +/- 0.5 kg of BW) were used in a 4 x 4 Latin square design with 21-d periods and a 2 x 2 factorial arrangement of dietary treatments. The dietary factors studied were 1) dry-rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 20 publications
7
25
1
Order By: Relevance
“…In the present work, a relationship was found between metabolic body weight and endogenous urinary crude protein that was five times greater than that reported by NRC (2007). This value may appear inconsistent; however, other reports in the literature present similar (Ghassemi Nejad et al, 2014) or even greater values than ours for other small ruminants (Kiran and Mutsvangwa, 2007), raising the hypothesis that the excretion of nitrogen is dependent on metabolic processes through which balance is achieved in response to a dietary change (Waterlow, 1999). Indeed, Bohnert et al (2011) reported a variation of N excreted in urine of 400% depending on dietary manipulation.…”
contrasting
confidence: 49%
See 2 more Smart Citations
“…In the present work, a relationship was found between metabolic body weight and endogenous urinary crude protein that was five times greater than that reported by NRC (2007). This value may appear inconsistent; however, other reports in the literature present similar (Ghassemi Nejad et al, 2014) or even greater values than ours for other small ruminants (Kiran and Mutsvangwa, 2007), raising the hypothesis that the excretion of nitrogen is dependent on metabolic processes through which balance is achieved in response to a dietary change (Waterlow, 1999). Indeed, Bohnert et al (2011) reported a variation of N excreted in urine of 400% depending on dietary manipulation.…”
contrasting
confidence: 49%
“…This difference may be explained by differences in the diet characteristics because the NRC (2007) reported a DM digestibility coefficient of 0.88, which is greater than that found here. In addition, Lobley et al (2000) and Kiran and Mutsvangwa (2007) reported greater values of nitrogen in feces, approximately 4% of the DMI. This fact raises the hypothesis that the relationship between DMI and fecal crude protein or nitrogen may be different for animals under different conditions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The increase of concentrate proportion in a forage based diet did not affect on CP apparent digestibility in goats (CantalapiedraHijar et al, 2009) and in dairy bulls (Wanapat et al, 2013). There is some controversy regarding to the CP digestiblity when portion of dietary forage is increased, which is likely due to the type of ingredients used in some experiments (Lu et al, 2005;Kiran and Mutsvangwa, 2007). Moreover, in this study, the experimental diets were designed to isonitrogenous (Table 2).…”
Section: Discussion Feed Intake and Apparent Digestibilitymentioning
confidence: 81%
“…Increasing concentrate proportion in grass hay based diet enhances urinary purine derivative significantly in goats (Cantalapiedra-Hijar et al, 2009). Processing of barley grain increases urinary purine derivatives slightly in rapidly growing lambs fed high nitrogen diets (Kiran and Mutsvangwa, 2007). Supplementation of barley grain enhances microbial protein synthesis in the rumen of steers fed low quality of forage (Marsetyo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%